Design of Web-Based Administrative Service Information System with Scrum Method - Sri Susanti, Nanda; Kusumawati, Serlie; Juwari, Juwari (LPPM STIKI Malang, 2024)
In the digital era, information systems have an important role in improving the efficiency of public services, including in administrative services. This research aims to develop a web-based administrative service system as a solution to manual systems that tend to be inefficient. The Scrum method was chosen as the development framework because of its flexibility in adapting to user needs as well as supporting collaboration and continuous improvement. The development stage starts from gathering user needs at the Product Backlog stage, followed by Sprint planning, Sprint implementation, to evaluation of work results through Sprint Review and Sprint Retrospective. The results of the development of this system show that the Scrum approach allows the integration of key features that make it easier to manage data and administrative services. The resulting system has succeeded in improving administrative efficiency and providing better accessibility for users. This research also provides insight into the implementation of the Scrum method in the development of web-based information systems, which can be applied to similar projects to improve the overall quality of public services.